Field of bones [compact disc, unabridged] - Jance, Judith A. (Jance, Judith A. Joanna Brady mysteries, 2018)
Sheriff Joanna Brady's best intentions to stay on maternity leave take a hit when a serial homicide case rocks Cochise County, dragging her into a far-reaching investigation to bring down a relentless killer.